Management of acute otitis externa using aural wick versus local drops - Qader, Shilan N.; Yaseen, Moyaser A. (Zanco Journal of Medical Sciences (ZJMS), 2012)
Background and objectives: Acute otitis externa is one the commonest otological disease. In this study we aimed to evaluate its types and the possible predisposing factors as well as comparing the effectiveness between local wick and local drops in treating acute otitis externa. Methods: A prospective analysis of 100 patients complained of acute otitis externa was performed in the department of Otolaryngology at Rizgary Teaching Hospital in Hawler between August 2005 to January 2006. Male patients were 45%, and the rest 55% were females. Patients were classified into two groups; 50 patients received topical application of cream using aural wick, and the second group of 50 patients treated by topical ear drops. Results: The commonest predisposing factors were water entrance to the affected ear during bathing and swimming (51%). On culturing, bacteria were found in 64% of patients and fungi in 11%. Topical application using aural wick showed 100% response, whereas only 60% of those received topical ear drops had an immediate response. Conclusion: Acute diffuse otitis externa is the most frequent type. Pseudomonas aeruginosa is the commonest bacterial growth. Aspergillous species is the commonest caused of fungal growth. Response to aural wick treatment is much better than aural drops.